TINGKAT KEJADIAN MISSFILE DI BAGIAN FILLING UNIT REKAM MEDIS RUMAH SAKIT UMUM DAERAH CIKALONG WETAN - Gunawan, Edih; Permana, Gilang Rahmat (Jurnal TEDC, 2023)
Based on observations in the medical record filling unit of the Cikalong Wetan Regional General Hospital, the authors found that the missfiled medical record document occurred due to the negligence of the filling officer in the process of storing medical record documents and the hospital information system was still in the process of being developed and the facilities and infrastructure in the filling had not yet been completed. complete so that it hampers the distribution process of medical record documents. This study aims to determine the incidence of missfiles in the medical record filling unit of the Cikalong Wetan Regional General Hospital. Based on the research that has been carried out, there are 26 medical record documents from 631 files that were examined, caused by the numbering system not according to SOPs, filing racks, document folders, expedition books that were still filled manually without using a tracer in the filling storage system, and human resources for filling officers who are inexperienced and lack discipline and responsibility in carrying out their duties as medical recorders.